Common Environmental Pollutants Negatively Affect Development and Regeneration in the Sea Anemone Nematostella vectensis Holobiont - Klein, Sylvia; Frazier, Victoria; Readdean, Timothy; Lucas, Emily; Diaz-Jimenez, Erica P.; Sogin, Mitchell; Ruff, Emil S.; Echeverri, Karen (Frontiers in Ecology and Evolution, 2021)
The anthozoan sea anemone Nematostella vectensis belongs to the phylum of cnidarians which also includes jellyfish and corals. Nematostella are native to US East Coast marsh lands, where they constantly adapt to changes in salinity, temperature, oxygen concentration and pH. Its natural ability to continually acclimate to changing environments coupled with its genetic tractability render Nematostella a powerful model organism in which to study the effects of common pollutants on the natural development of these animals. Potassium nitrate, commonly used in fertilizers, and Phthalates, a component of plastics are frequent environmental stressors found in coastal and marsh waters. Here we present data showing how early exposure to these pollutants leads to dramatic defects in development of the embryos and eventual mortality possibly due to defects in feeding ability. Additionally, we examined the microbiome of the animals and identified subtle shifts in the microbial community that correlate with the type of water they grew in and their exposure to pollutants.